Feedback of Individual Genetic and Genomics Research Results: A Qualitative Study Involving Grassroots Communities in Uganda - Ochieng, Joseph; Kwagala, Betty; Barugahre, John; Möller, Marlo; Moodley, Keymanthri (medRxiv, 2022)
Genetics and genomics research (GGR) is associated with several challenges including, but not limited to, implications of sharing research findings with participants and their family members, issues of confidentiality, determining appropriate methods for providing genetic or genomic information to individuals tested, and ownership of DNA obtained from the samples. Additionally, GGR holds significant potential risk for social and psychological harms. A considerable amount of research has been conducted with resultant literature and global debate on return of genetic and genomics testing results, but such investigations are limited in the African setting, including Uganda. The objective of the study was to assess perceptions of grassroots communities on if and how feedback of individual genetics and genomics testing results should be carried out in a Ugandan setting. Methods: This was a cross-sectional study that employed a qualitative exploratory approach. A total of 42 individuals from grassroots communities representing three major ethnic groupings participated in five deliberative focus group discussions. Data were analysed through content analysis along the main themes of the study. NVivo software (QSR international 2020) was used to support data analysis and illustrative quotes were extracted.
Keywords: Feedback; Individual Genetic and Genomic Research Results; Grassroots Communities